Determinan Audit Going Concern Perusahaan Manufaktur Di Indonesia - Nurhidayah Nurhidayah (Musamus University, 2019)
This research aims to find the determinants of affecting audit going concern of manufacturing firms in Indonesia. The manufacturing firms listed in Indonesian Stock Exchange become the sample of this research. The data are processed using descriptive statistics and tested using logistic regression. The results find that firms’ growth, profitability, and solvability can not affect the audit going concern, but liquidity is found to affect audit going concern. The implication of this research is addressed to the firm which should keep the going concern, not only for the sake of the image to the investment , but it also for operasional activities with paying the attention of some financial ratios in this research. Keywords: firms’ growth, profitability, liquidity, solvability, audit going concern.